INVESTIGATION OF BIO-OIL EXTRACTION FROM DELIGNIFIED EMPTY FRUIT BUNCH (EFB) VIA SUPERCRITICAL CARBON DIOXIDE AND SOXHLET EXTRACTION - NGU, JENNIE SIEW ZHEN (2023)
This research study focuses on the utilization of empty fruit bunch (EFB) as the feedstock for producing high-quality bio-oil. This was achieved through the utilization of supercritical carbon dioxide SCCO2 and Soxhlet extraction by removing the lignin using a low transition temperature mixture (LTTM).